Association between a polymorphic variant in the CDKN2B-AS1/ANRIL gene and pancreatic cancer risk - Giaccherini, Matteo; Farinella, Riccardo; Gentiluomo, Manuel; Mohelnikova-Duchonova, Beatrice; Kauffmann, Emanuele Federico; Palmeri, Matteo; Uzunoglu, Faik; Soucek, Pavel; Petrauskas, Dalius; Cavestro, Giulia Martina; Zykus, Romanas; Carrara, Silvia; et al. (International journal of cancer, 2023)
Genes carrying high-penetrance germline mutations may also be associated with cancer susceptibility through common low-penetrance genetic variants. To increase the knowledge on genetic pancreatic ductal adenocarcinoma (PDAC) aetiology, the common genetic variability of PDAC familial genes was analysed in our study. We conducted a multiphase study analysing 7745 single nucleotide polymorphisms (SNPs) from 29 genes reported to harbour a high-penetrance PDAC-associated mutation in at least one published study. To assess the effect of the SNPs on PDAC risk, a total of 14 666 PDAC cases and 221 897 controls across five different studies were analysed. The T allele of the rs1412832 polymorphism, that is situated in the CDKN2B-AS1/ANRIL, showed a genome-wide significant association with increased risk of developing PDAC (OR = 1.11, 95% CI = 1.07-1.15, P = 5.25 × 10-9 ). CDKN2B-AS1/ANRIL is a long noncoding RNA, situated in 9p21.3, and regulates many target genes, among which CDKN2A (p16) that frequently shows deleterious somatic and germline mutations and deregulation in PDAC. Our results strongly support the role of the genetic variability of the 9p21.3 region in PDAC aetiopathogenesis and highlight the importance of secondary analysis as a tool for discovering new risk loci in complex human diseases.
Keywords: RNA dlouhá nekódující; genetic susceptibility; duktální karcinom slinivky břišní; pancreatic ductal adenocarcinoma; jednonukleotidový polymorfismus; Carcinoma, Pancreatic Ductal; association study; Polymorphism, Single Nucleotide; nádory slinivky břišní; Humans; lidé; Pancreatic Neoplasms; single nucleotide polymorphisms; Genetic Predisposition to Disease; genetická predispozice k nemoci; RNA, Long Noncoding